2014
DOI: 10.4103/0975-7406.137415
|View full text |Cite
|
Sign up to set email alerts
|

Morphological alterations in the dentition of type I diabetes mellitus patients

Abstract: Introduction:Type 1 diabetes mellitus (DM) is an endocrine disorder that occurs commonly in an age group, where the development of primary and permanent dentition takes place. As altered endocrine functions may affect the shape and size of teeth leading to dental anomalies, this study was conducted to look for the occurrence of any dental anomalies in type I DM patients.Materials and Methods:A diabetic camp was conducted at Alur Chandrashekharappa Memorial Hospital, Davangere, where 30 diabetic patients were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…Sixth cusp in mandibular first molar, termed as tuberculum intermedium[ 19 ] was noted in one case and literature had related this anomaly with metabolic disorders like type I diabetes mellitus. [ 20 ] A single case of dens evaginatus (central tubercle or Leong's premolar) was observed unilaterally in mandibular second premolar [ Figure 4 ]. Anticipating periodontal problems, due to improper occlusal force, grinding of opposing teeth or this tubercle can be done.…”
Section: Discussionmentioning
confidence: 99%
“…Sixth cusp in mandibular first molar, termed as tuberculum intermedium[ 19 ] was noted in one case and literature had related this anomaly with metabolic disorders like type I diabetes mellitus. [ 20 ] A single case of dens evaginatus (central tubercle or Leong's premolar) was observed unilaterally in mandibular second premolar [ Figure 4 ]. Anticipating periodontal problems, due to improper occlusal force, grinding of opposing teeth or this tubercle can be done.…”
Section: Discussionmentioning
confidence: 99%
“…In Type 1 diabetes mellitus, the presence of six cusps and four cusps in mandibular first molars, prominent cusp of Carabelli in maxillary molars are observed. [ 23 ] Animal studies have shown that hyperglycemic environment affects the phenotype of resulting teeth by epigenetic alterations. [ 13 ]…”
Section: Olar M Alformations In V Arious S Ystemic D Iseasesmentioning
confidence: 99%
“…Oral screening examinations conducted by Yamunadevi et al [30] showed a number of changes in the morphology of teeth of patients with diagnosed diabetes mellitus type 1. Among them the presence of additional (sixth) cusps in the first mandibular molars is worth noting, which the authors found in 7 of 30 patients studied, including in 5 patients midline cusps (tuberculum interlude), located on the lingual surfaces of molars, and two other cases of the 6 th cusps included cusps located on the edge of the marginal distal lower molars (tuberculum sextum).…”
Section: Changes In the Morphological Structure Of Human Teeth In Typmentioning
confidence: 99%
“…Chronic hyperglycaemia is associated with the dysfunction of, damage to and failure of various organs, particularly eyes, nerves, the heart and blood vessels. Type 1 diabetes (insulin-dependent) is less frequent than type 2 diabetes and accounts for 5-15% of all cases of diabetes [30]. Usually it develops in young people, when the development of deciduous and permanent teeth takes place.…”
Section: Introductionmentioning
confidence: 99%